Розробка компонентів інформаційної системи онлайн орендування місця для паркування автомобіля - Жемчужний, Р. І. (ХНУРЕ, 2024)
This work focuses on the development of components for an online parking reservation information system. The intricate interplay of various factors in urban transportation demands a systematic approach to efficiently manage parking spaces. The research delves into both the internal and external factors affecting the functionality of the online parking reservation system. Examining the challenges inherent in the parking system, the study identifies potential threats and vulnerabilities.
Keywords: онлайн орендування місця; паркування